Omega-3 Polyunsaturated Fatty Acid Intervention Against Established Autoimmunity in a Murine Model of Toxicant-Triggered Lupus - Pestka, James J.; Akbari, Peyman; Wierenga, Kathryn A.; Bates, Melissa A.; Gilley, Kristen. N.; Wagner, James G.; Lewandowski, Ryan P.; Rajasinghe, Lichchavi D.; Chauhan, Preeti S.; Lock, Adam L.; Li, Quan-Zhen; Harkema, Jack R. (Frontiers in Immunology, 2021)
Workplace exposure to respirable crystalline silica dust (cSiO2) has been etiologically linked to the development of lupus and other human autoimmune diseases. Lupus triggering can be recapitulated in female NZBWF1 mice by four weekly intranasal instillations with 1 mg cSiO2. This elicits inflammatory/autoimmune gene expression and ectopic lymphoid structure (ELS) development in the lung within 1 wk, ultimately driving early onset of systemic autoimmunity and glomerulonephritis. Intriguingly, dietary supplementation with docosahexaenoic acid (DHA), an ω-3 polyunsaturated fatty acid (PUFA) found in fish oil, beginning 2 wk prior to cSiO2 challenge, prevented inflammation and autoimmune flaring in this novel model. However, it not yet known how ω-3 PUFA intervention influences established autoimmunity in this murine model of toxicant-triggered lupus. Here we tested the hypothesis that DHA intervention after cSiO2-initiated intrapulmonary autoimmunity will suppress lupus progression in the NZBWF1 mouse. Six-wk old NZWBF1 female mice were fed purified isocaloric diet for 2 wk and then intranasally instilled with 1 mg cSiO2 or saline vehicle weekly for 4 consecutive wk. One wk after the final instillation, which marks onset of ELS formation, mice were fed diets supplemented with 0, 4, or 10 g/kg DHA. One cohort of mice (n=8/group) was terminated 13 wk after the last cSiO2 instillation and assessed for autoimmune hallmarks. A second cohort of mice (n=8/group) remained on experimental diets and was monitored for proteinuria and moribund criteria to ascertain progression of glomerulonephritis and survival, respectively. DHA consumption dose-dependently increased ω-3 PUFA content in the plasma, lung, and kidney at the expense of the ω-6 PUFA arachidonic acid. Dietary intervention with high but not low DHA after cSiO2 treatment suppressed or delayed: i) recruitment of T cells and B cells to the lung, ii) development of pulmonary ELS, iii) elevation of a wide spectrum of plasma autoantibodies associated with lupus and other autoimmune diseases, iv) initiation and progression of glomerulonephritis, and v) onset of the moribund state. Taken together, these preclinical findings suggest that DHA supplementation at human caloric equivalent of 5 g/d was an effective therapeutic regimen for slowing progression of established autoimmunity triggered by the environmental toxicant cSiO2.